Coated hard alloy cutter

By using tungsten carbide-based carbide as the substrate in coated carbide tools, and depositing multi-coated molybdenum sulfide, aluminum nitride and aluminum nitride titanium-silicon nitride multi-coats through chemical vapor deposition processes, the coating and matrix bonding force is solved. The poor problem significantly improves the hardness and service life of the tool.

CN119194195APending Publication Date: 2024-12-27ZHEJIANG HENGCHENG CEMENTED CARBIDE CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411209681.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Under the impact load and cutting force of existing coated carbide tools, the poor bonding force between the coating and the substrate leads to crack propagation and rupture, resulting in tool failure.

Method used

Using tungsten carbide-based cemented carbide as the matrix, a multi-coat is deposited through a chemical vapor deposition process. The coatings are molybdenum sulfide, aluminum nitride and aluminum titanium silicon from the inside to the outside, optimizing the relative atomic content and thickness of each layer. , a gradient structure is formed to improve interface bonding and compatibility.

Benefits of technology

It effectively enhances the bonding tightness and hardness of the coating interface, improves the service life and wear resistance of the tool, and significantly extends the service life of the tool.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005020015940000111
    Figure BDA0005020015940000111
Patent Text Reader

Abstract

The invention relates to the field of cutter coatings, and provides a coated hard alloy cutter aiming at the problem that the mechanical property of the cutter is influenced by poor binding force between the coating and a substrate, the cutter substrate is tungsten carbide-based hard alloy, and the hard alloy contains VC, Ru and TaC; and the coating sequentially comprises a molybdenum sulfide layer, an aluminum nitride layer and an aluminum titanium silicon nitride layer from inside to outside. By limiting the components of the cutter base body and the sequence and components of the multi-element coating, the cutter with good binding force between the coating and the base body and long service life is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of tool coatings, in particular to a coated cemented carbide tool. Background Art

[0002] Coated carbide tools are obtained by coating a thin layer of refractory metal or non-metallic compound with good wear resistance on the surface of a carbide substrate with good strength and toughness by using methods such as vapor deposition. For example, patent CN105479318B discloses a post-processing method for carbide coated tools and carbide coated tools. The coating acts as a chemical barrier and thermal barrier, reducing the diffusion and chemical reaction between the tool and the workpiece, thereby reducing the wear of the crescent groove. Coated carbide tools have the characteristics of high surface hardness, good wear resistance, stable chemical properties, heat and oxidation resistance, low friction coefficient and low thermal conductivity. Compared with uncoated tools, the tool life can be increased by more than 3 to 5 times during cutting, the cutting speed can be increased by 20% to 70%, the processing accuracy can be increased by 0.5 to 1 level, and the tool consumption cost can be reduced by 20% to 50%. Therefore, coated tools have become the symbol of modern cutting tools, and the proportion of use in tools has exceeded 50%.

[0003] According to the service environment and failure analysis of cemented carbide coated blades, when the hard coating is combined with a hard substrate (tungsten-titanium-cobalt cemented carbide), under the impact load, due to the poor toughness of the substrate, the cracks generated in the coating are easy to expand into the substrate, causing the blade to break and fail. When the hard coating is combined with a soft substrate (tungsten-cobalt cemented carbide), under the action of cutting force, due to the poor ability of the substrate to resist plastic deformation, the coating shell is easy to crack, causing the coating to fail. For example, patent CN discloses. Therefore, an ideal solution is needed. Summary of the invention

[0004] In order to overcome the problem that the poor bonding between the coating and the substrate affects the mechanical properties of the tool, the present invention provides a coated cemented carbide tool. By limiting the components of the tool substrate and the order and components of the multi-layer coating, a tool with good bonding between the coating and the substrate and a long service life is obtained.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: A coated cemented carbide tool has a tool substrate of tungsten carbide-based cemented carbide containing VC, Ru and TaC; the coating comprises a molybdenum sulfide layer, an aluminum nitride layer and an aluminum titanium silicon nitride layer from the inside to the outside.

[0006] Preferably, the relative atomic content of each element in the aluminum titanium silicon nitride layer is Ti 30-40%, Al 18-25%, Si 2-5%, and the balance is N.

[0007] As a further preference, the relative atomic content of each element in the aluminum titanium silicon nitride layer is Ti 35-40%, Al 20-25%, Si 2-3%, and the balance is N.

[0008] Preferably, the total thickness of the coating is 5-10 μm.

[0009] Preferably, the thickness of the molybdenum sulfide layer is 0.5-4 μm, the thickness of the aluminum nitride layer is 2-5 μm, and the thickness of the aluminum titanium silicon nitride layer is 2.5-7.5 μm.

[0010] Preferably, the thickness of the aluminum nitride layer is 2-4 times the thickness of the molybdenum sulfide layer, and the thickness of the aluminum titanium silicon nitride layer is 5-8 times the thickness of the molybdenum sulfide layer.

[0011] Preferably, the coating is deposited by a chemical vapor deposition process.

[0012] The specific components of the tool matrix are: 82-91.5wt% tungsten carbide, 8-15wt% binder, 0.5-3wt% regulator, the sum of the mass percentages of the three is 100wt%, and the regulator is composed of VC, Ru and TaC.

[0013] Preferably, the mass ratio of VC, Ru and TaC in the regulator is (1-6):(5-8):10.

[0014] Preferably, the binder is one or more of cobalt, iron, manganese, copper and nickel.

[0015] Therefore, the beneficial effects of the present invention are as follows: the present invention is a three-coated tool, and the multi-layer coating interrupts the growth of columnar crystals in the coating interface, so that the coating interface is strengthened, the grains are tightly bonded, and the hardness of the coating is improved. Molybdenum sulfide bonds the bottom layer, plays a transitional role between the substrate and the main coating, improves the interface bonding force between the main coating and the substrate, and improves the bonding performance between the film / substrate. The role of the aluminum nitride layer, on the one hand, oxygen atoms enter the aluminum nitride layer lattice to produce lattice distortion, which plays a role of solid solution strengthening, making the coating structure dense and the hardness improved; on the other hand, as an intermediate layer, it plays a role of "bridging the upper and lower", so that the gradient coating composition changes continuously, improves the compatibility between each coating, reduces the thermal stress generated by the difference in thermal expansion coefficients of different coatings, makes each coating bond well, and improves the film-base bonding force of the multi-layer coating. The aluminum titanium silicon nitride layer coating has extremely high hardness, wear resistance and heat resistance, so it is placed on the outermost side to significantly improve the service life of the tool. DETAILED DESCRIPTION

[0016] The technical solution of the present invention is further described below through specific embodiments.

[0017] In the present invention, unless otherwise specified, the raw materials and equipment used can be purchased from the market or are commonly used in the art. The methods in the embodiments, unless otherwise specified, are all conventional methods in the art. Unless otherwise specified, parts are all weight parts, temperatures are expressed in ° C or at ambient temperature, and pressures are atmospheric pressure or near atmospheric pressure. There are many variations and combinations of reaction conditions (such as component concentrations, desired solvents, solvent mixtures, temperatures, pressures, and other reaction ranges) and conditions that can be used to optimize the purity and yield of the product obtained by the method, and only reasonable routine experiments will be required to optimize such method conditions.

[0018] Example A coated cemented carbide tool consists of a tool substrate and a coating. The coating is deposited on the surface of the tool substrate by a conventional chemical vapor deposition process.

[0019] 1. Tool base The tool matrix is ​​a tungsten carbide-based hard alloy. The specific components of the tool matrix are: 82-91.5wt% tungsten carbide, 8-15wt% binder, 0.5-3wt% regulator, the sum of the three mass percentages is 100wt%, wherein the regulator is composed of vanadium carbide, ruthenium, and tantalum carbide in a mass ratio of (1-6):(5-8):10.

[0020] Binders mainly provide ductility, toughness and strength to the alloy. Common metal binders include cobalt (Co), iron (Fe), manganese (Mn), copper (Cu), and nickel (Ni).

[0021] 2. Coating The coatings are molybdenum sulfide (MoS 2 ) layer, aluminum nitride (AlN) layer and aluminum titanium silicon nitride (TiAlSiN) layer. The relative atomic content of each element in the aluminum titanium silicon nitride layer is Ti 30-40%, Al 18-25%, Si 2-5%, and the balance is N; the relative atomic content of each element is further preferably Ti 35-40%, Al 20-25%, Si 2-3%, and the balance is N. The total thickness of the coating is 5-10μm. Among them, molybdenum sulfide (MoS 2 ) layer has a thickness of 0.5-4 μm, the thickness of the aluminum nitride layer is 2-5 μm, and the thickness of the aluminum titanium silicon nitride layer is 2.5-7.5 μm. As a further preference, the thickness of the aluminum nitride layer is 2-4 times the thickness of the molybdenum sulfide layer, and the thickness of the aluminum titanium silicon nitride layer is 5-8 times the thickness of the molybdenum sulfide layer.

[0022] The molybdenum sulfide layer connects the substrate and the aluminum nitride layer. The thinner the better. A thicker aluminum titanium silicon nitride layer will affect the mechanical properties. The thicker the aluminum titanium silicon nitride layer is, the better the protection of the tool. The preferred coating of the present invention is thickened from the inside to the outside, which can reduce the thermal stress caused by the difference in thermal expansion coefficient, thereby improving the interlayer bonding strength and tool life.

[0023] Example 1 A coated cemented carbide tool consists of a tool substrate and a coating. The coating is deposited on the surface of the tool substrate by a conventional chemical vapor deposition process.

[0024] 1. Tool base The tool matrix is ​​a tungsten carbide-based cemented carbide. The specific components of the tool matrix are: 90wt% tungsten carbide, 9wt% binder, 1wt% regulator, and the sum of the three mass percentages is 100wt%. Among them, the regulator is composed of vanadium carbide, ruthenium, and tantalum carbide in a mass ratio of 5:7:10; the binder is cobalt powder.

[0025] 2. Coating The coating is composed of a molybdenum sulfide layer, an aluminum nitride layer, and an aluminum titanium silicon nitride layer from the inside to the outside, wherein the relative atomic content of each element in the aluminum titanium silicon nitride layer is Ti 35%, Al 20%, Si 2%, and N 43%.

[0026] The total thickness of the coating is 10 μm, of which the thickness of the molybdenum sulfide layer is 1 μm, the thickness of the aluminum nitride layer is 4 μm (4 times the thickness of the molybdenum sulfide layer), and the thickness of the aluminum titanium silicon nitride layer is 5 μm (5 times the thickness of the molybdenum sulfide layer).

[0027] Example 2 A coated cemented carbide tool consists of a tool substrate and a coating. The coating is deposited on the surface of the tool substrate by a conventional chemical vapor deposition process.

[0028] 1. Tool base The tool matrix is ​​a tungsten carbide-based cemented carbide. The specific components of the tool matrix are: 82wt% tungsten carbide, 15wt% binder, 3wt% regulator, and the sum of the three mass percentages is 100wt%. Among them, the regulator is composed of vanadium carbide, ruthenium, and tantalum carbide in a mass ratio of 1:5:10; the binder is cobalt powder.

[0029] 2. Coating The coating is composed of a molybdenum sulfide layer, an aluminum nitride layer, and an aluminum titanium silicon nitride layer from the inside to the outside, wherein the relative atomic content of each element in the aluminum titanium silicon nitride layer is Ti 40%, Al 25%, Si 3%, and N 32%.

[0030] The total thickness of the coating is 5 μm, of which the thickness of the molybdenum sulfide layer is 0.5 μm, the thickness of the aluminum nitride layer is 2 μm (4 times the thickness of the molybdenum sulfide layer), and the thickness of the aluminum titanium silicon nitride layer is 2.5 μm (5 times the thickness of the molybdenum sulfide layer).

[0031] Example 3 A coated cemented carbide tool consists of a tool substrate and a coating. The coating is deposited on the surface of the tool substrate by a conventional chemical vapor deposition process.

[0032] 1. Tool base The tool matrix is ​​a tungsten carbide-based cemented carbide. The specific components of the tool matrix are: 91.5wt% tungsten carbide, 8wt% binder, 0.5wt% regulator, and the sum of the three mass percentages is 100wt%. Among them, the regulator is composed of vanadium carbide, ruthenium, and tantalum carbide in a mass ratio of 6:8:10; the binder is cobalt powder.

[0033] 2. Coating The coating is composed of a molybdenum sulfide layer, an aluminum nitride layer, and an aluminum titanium silicon nitride layer from the inside to the outside, wherein the relative atomic content of each element in the aluminum titanium silicon nitride layer is Ti 30%, Al 18%, Si 5%, and N 47%.

[0034] The total thickness of the coating is 8 μm, of which the thickness of the molybdenum sulfide layer is 1 μm, the thickness of the aluminum nitride layer is 2 μm (twice the thickness of the molybdenum sulfide layer), and the thickness of the aluminum titanium silicon nitride layer is 5 μm (five times the thickness of the molybdenum sulfide layer).

[0035] Example 4 The difference from Example 1 is that the relative atomic content of Ti element in the aluminum titanium silicon nitride layer of the coating is less than 20%. The details are as follows: A coated cemented carbide tool comprises a tool substrate and a coating, and the coating is deposited on the surface of the tool substrate by a conventional chemical vapor deposition process.

[0036] 1. Tool base The tool matrix is ​​a tungsten carbide-based cemented carbide. The specific components of the tool matrix are: 90wt% tungsten carbide, 9wt% binder, 1wt% regulator, and the sum of the three mass percentages is 100wt%. Among them, the regulator is composed of vanadium carbide, ruthenium, and tantalum carbide in a mass ratio of 5:7:10; the binder is cobalt powder.

[0037] 2. Coating The coating is composed of a molybdenum sulfide layer, an aluminum nitride layer and an aluminum titanium silicon nitride layer from the inside to the outside, wherein the relative atomic content of each element in the aluminum titanium silicon nitride layer is Ti 20%, Al 20%, Si 2%, and N 58%.

[0038] The total thickness of the coating is 10 μm, of which the thickness of the molybdenum sulfide layer is 1 μm, the thickness of the aluminum nitride layer is 4 μm (4 times the thickness of the molybdenum sulfide layer), and the thickness of the aluminum titanium silicon nitride layer is 5 μm (5 times the thickness of the molybdenum sulfide layer).

[0039] Example 5 The difference from Example 1 is that the relative atomic content of Al in the aluminum titanium silicon nitride layer is less than 10%. The details are as follows: A coated cemented carbide tool comprises a tool substrate and a coating, and the coating is deposited on the surface of the tool substrate by a conventional chemical vapor deposition process.

[0040] 1. Tool base The tool matrix is ​​a tungsten carbide-based cemented carbide. The specific components of the tool matrix are: 90wt% tungsten carbide, 9wt% binder, 1wt% regulator, and the sum of the three mass percentages is 100wt%. Among them, the regulator is composed of vanadium carbide, ruthenium, and tantalum carbide in a mass ratio of 5:7:10; the binder is cobalt powder.

[0041] 2. Coating The coating is composed of a molybdenum sulfide layer, an aluminum nitride layer, and an aluminum titanium silicon nitride layer from the inside to the outside, wherein the relative atomic content of each element in the aluminum titanium silicon nitride layer is Ti 35%, Al 10%, Si 2%, and N 53%.

[0042] The total thickness of the coating is 10 μm, of which the thickness of the molybdenum sulfide layer is 1 μm, the thickness of the aluminum nitride layer is 4 μm (4 times the thickness of the molybdenum sulfide layer), and the thickness of the aluminum titanium silicon nitride layer is 5 μm (5 times the thickness of the molybdenum sulfide layer).

[0043] Example 6 The difference from Example 1 is that the relative atomic content of Si element in the aluminum titanium silicon nitride layer of the coating is higher at 8%. The details are as follows: A coated cemented carbide tool comprises a tool substrate and a coating, and the coating is deposited on the surface of the tool substrate by a conventional chemical vapor deposition process.

[0044] 1. Tool base The tool matrix is ​​a tungsten carbide-based cemented carbide. The specific components of the tool matrix are: 90wt% tungsten carbide, 9wt% binder, 1wt% regulator, and the sum of the three mass percentages is 100wt%. Among them, the regulator is composed of vanadium carbide, ruthenium, and tantalum carbide in a mass ratio of 5:7:10; the binder is cobalt powder.

[0045] 2. Coating The coating is composed of a molybdenum sulfide layer, an aluminum nitride layer and an aluminum titanium silicon nitride layer from the inside to the outside, wherein the relative atomic content of each element in the aluminum titanium silicon nitride layer is Ti 35%, Al 20%, Si 8%, and N 37%.

[0046] The total thickness of the coating is 10 μm, of which the thickness of the molybdenum sulfide layer is 1 μm, the thickness of the aluminum nitride layer is 4 μm (4 times the thickness of the molybdenum sulfide layer), and the thickness of the aluminum titanium silicon nitride layer is 5 μm (5 times the thickness of the molybdenum sulfide layer).

[0047] Example 7 The difference from Example 1 is that the thickness of the molybdenum sulfide layer is 5 μm. The details are as follows: A coated cemented carbide tool consists of a tool substrate and a coating. The coating is deposited on the surface of the tool substrate by a conventional chemical vapor deposition process.

[0048] 1. Tool base The tool matrix is ​​a tungsten carbide-based cemented carbide. The specific components of the tool matrix are: 90wt% tungsten carbide, 9wt% binder, 1wt% regulator, and the sum of the three mass percentages is 100wt%. Among them, the regulator is composed of vanadium carbide, ruthenium, and tantalum carbide in a mass ratio of 5:7:10; the binder is cobalt powder.

[0049] 2. Coating The coating is composed of a molybdenum sulfide layer, an aluminum nitride layer, and an aluminum titanium silicon nitride layer from the inside to the outside, wherein the relative atomic content of each element in the aluminum titanium silicon nitride layer is Ti 35%, Al 20%, Si 2%, and N 43%.

[0050] The total thickness of the coating is 19 μm, of which the thickness of the molybdenum sulfide layer is 5 μm, the thickness of the aluminum nitride layer is 4 μm, and the thickness of the aluminum titanium silicon nitride layer is 5 μm.

[0051] Example 8 The difference from Example 1 is that the thickness of the aluminum nitride layer is 1 times that of the molybdenum sulfide layer. A coated cemented carbide tool consists of a tool substrate and a coating. The coating is deposited on the surface of the tool substrate by a conventional chemical vapor deposition process.

[0052] 1. Tool base The tool matrix is ​​a tungsten carbide-based cemented carbide. The specific components of the tool matrix are: 90wt% tungsten carbide, 9wt% binder, 1wt% regulator, and the sum of the three mass percentages is 100wt%. Among them, the regulator is composed of vanadium carbide, ruthenium, and tantalum carbide in a mass ratio of 5:7:10; the binder is cobalt powder.

[0053] 2. Coating The coating is composed of a molybdenum sulfide layer, an aluminum nitride layer, and an aluminum titanium silicon nitride layer from the inside to the outside, wherein the relative atomic content of each element in the aluminum titanium silicon nitride layer is Ti 35%, Al 20%, Si 2%, and N 43%.

[0054] The total thickness of the coating is 10 μm, of which the thickness of the molybdenum sulfide layer is 1 μm, the thickness of the aluminum nitride layer is 1 μm (1 times the thickness of the molybdenum sulfide layer), and the thickness of the aluminum titanium silicon nitride layer is 8 μm (8 times the thickness of the molybdenum sulfide layer).

[0055] Example 9 The difference from Example 1 is that the thickness of the aluminum titanium silicon nitride layer is 4 times that of the molybdenum sulfide layer, which is the same as the thickness of the aluminum nitride layer. A coated cemented carbide tool consists of a tool substrate and a coating. The coating is deposited on the surface of the tool substrate by a conventional chemical vapor deposition process.

[0056] 1. Tool base The tool matrix is ​​a tungsten carbide-based cemented carbide. The specific components of the tool matrix are: 90wt% tungsten carbide, 9wt% binder, 1wt% regulator, and the sum of the three mass percentages is 100wt%. Among them, the regulator is composed of vanadium carbide, ruthenium, and tantalum carbide in a mass ratio of 5:7:10; the binder is cobalt powder.

[0057] 2. Coating The coating is composed of a molybdenum sulfide layer, an aluminum nitride layer, and an aluminum titanium silicon nitride layer from the inside to the outside, wherein the relative atomic content of each element in the aluminum titanium silicon nitride layer is Ti 35%, Al 20%, Si 2%, and N 43%.

[0058] The total thickness of the coating is 9 μm, of which the thickness of the molybdenum sulfide layer is 1 μm, the thickness of the aluminum nitride layer is 4 μm (4 times the thickness of the molybdenum sulfide layer), and the thickness of the aluminum titanium silicon nitride layer is 4 μm (4 times the thickness of the molybdenum sulfide layer).

[0059] Example 10 The difference from Example 1 is that the thickness of the aluminum titanium silicon nitride layer is 4 times that of the molybdenum sulfide layer, and the thickness of the aluminum nitride layer is 5 times that of the molybdenum sulfide layer. The details are as follows: A coated cemented carbide tool consists of a tool substrate and a coating. The coating is deposited on the surface of the tool substrate by a conventional chemical vapor deposition process.

[0060] 1. Tool base The tool matrix is ​​a tungsten carbide-based cemented carbide. The specific components of the tool matrix are: 90wt% tungsten carbide, 9wt% binder, 1wt% regulator, and the sum of the three mass percentages is 100wt%. Among them, the regulator is composed of vanadium carbide, ruthenium, and tantalum carbide in a mass ratio of 5:7:10; the binder is cobalt powder.

[0061] 2. Coating The coating is composed of a molybdenum sulfide layer, an aluminum nitride layer, and an aluminum titanium silicon nitride layer from the inside to the outside, wherein the relative atomic content of each element in the aluminum titanium silicon nitride layer is Ti 35%, Al 20%, Si 2%, and N 43%.

[0062] The total thickness of the coating is 10 μm, of which the thickness of the molybdenum sulfide layer is 1 μm, the thickness of the aluminum nitride layer is 5 μm (5 times the thickness of the molybdenum sulfide layer), and the thickness of the aluminum titanium silicon nitride layer is 4 μm (4 times the thickness of the molybdenum sulfide layer).

[0063] Comparative Example Comparative Example 1 The difference from Example 1 is that the tool has no coating.

[0064] Comparative Example 2 The difference from Example 1 is that there is no molybdenum sulfide layer in the coating. A coated cemented carbide tool consists of a tool substrate and a coating. The coating is deposited on the surface of the tool substrate by a conventional chemical vapor deposition process.

[0065] 1. Tool base The tool matrix is ​​a tungsten carbide-based cemented carbide. The specific components of the tool matrix are: 90wt% tungsten carbide, 9wt% binder, 1wt% regulator, and the sum of the three mass percentages is 100wt%. Among them, the regulator is composed of vanadium carbide, ruthenium, and tantalum carbide in a mass ratio of 5:7:10; the binder is cobalt powder.

[0066] 2. Coating The coating is composed of an aluminum nitride layer and an aluminum titanium silicon nitride layer from the inside to the outside, wherein the relative atomic content of each element in the aluminum titanium silicon nitride layer is Ti 35%, Al 20%, Si 2%, and N 43%.

[0067] The total thickness of the coating is 10 μm, of which the thickness of the aluminum nitride layer is 5 μm and the thickness of the aluminum titanium silicon nitride layer is 5 μm.

[0068] Comparative Example 3 The difference from Example 1 is that there is no aluminum nitride layer in the coating. The details are as follows: A coated cemented carbide tool consists of a tool substrate and a coating. The coating is deposited on the surface of the tool substrate by a conventional chemical vapor deposition process.

[0069] 1. Tool base The tool matrix is ​​a tungsten carbide-based cemented carbide. The specific components of the tool matrix are: 90wt% tungsten carbide, 9wt% binder, 1wt% regulator, and the sum of the three mass percentages is 100wt%. Among them, the regulator is composed of vanadium carbide, ruthenium, and tantalum carbide in a mass ratio of 5:7:10; the binder is cobalt powder.

[0070] 2. Coating The coating is composed of a molybdenum sulfide layer and an aluminum titanium silicon nitride layer from the inside to the outside, wherein the relative atomic content of each element in the aluminum titanium silicon nitride layer is Ti 35%, Al 20%, Si 2%, and N 43%.

[0071] The total thickness of the coating is 10 μm, of which the thickness of the molybdenum sulfide layer is 1 μm and the thickness of the aluminum titanium silicon nitride layer is 9 μm.

[0072] Comparative Example 4 The difference from Example 1 is that there is no aluminum titanium silicon nitride layer in the coating. A coated cemented carbide tool consists of a tool substrate and a coating. The coating is deposited on the surface of the tool substrate by a conventional chemical vapor deposition process.

[0073] 1. Tool base The tool matrix is ​​a tungsten carbide-based cemented carbide. The specific components of the tool matrix are: 90wt% tungsten carbide, 9wt% binder, 1wt% regulator, and the sum of the three mass percentages is 100wt%. Among them, the regulator is composed of vanadium carbide, ruthenium, and tantalum carbide in a mass ratio of 5:7:10; the binder is cobalt powder.

[0074] 2. Coating The coatings are molybdenum sulfide layer and aluminum nitride layer from inside to outside.

[0075] The total thickness of the coating is 10 μm, of which the thickness of the molybdenum sulfide layer is 1 μm and the thickness of the aluminum nitride layer is 9 μm.

[0076] Comparative Example 5 The difference from Example 1 is that the coating is composed of a molybdenum sulfide layer, an aluminum titanium silicon nitride layer, and an aluminum nitride layer from the inside to the outside. The details are as follows: A coated cemented carbide tool consists of a tool substrate and a coating. The coating is deposited on the surface of the tool substrate by a conventional chemical vapor deposition process.

[0077] 1. Tool base The tool matrix is ​​a tungsten carbide-based cemented carbide. The specific components of the tool matrix are: 90wt% tungsten carbide, 9wt% binder, 1wt% regulator, and the sum of the three mass percentages is 100wt%. Among them, the regulator is composed of vanadium carbide, ruthenium, and tantalum carbide in a mass ratio of 5:7:10; the binder is cobalt powder.

[0078] 2. Coating The coating is composed of a molybdenum sulfide layer, an aluminum titanium silicon nitride layer and an aluminum nitride layer from the inside to the outside, wherein the relative atomic content of each element in the aluminum titanium silicon nitride layer is Ti 35%, Al 20%, Si 2%, and N 43%.

[0079] The total thickness of the coating is 10 μm, of which the thickness of the molybdenum sulfide layer is 1 μm, the thickness of the aluminum nitride layer is 4 μm (4 times the thickness of the molybdenum sulfide layer), and the thickness of the aluminum titanium silicon nitride layer is 5 μm (5 times the thickness of the molybdenum sulfide layer).

[0080] Comparative Example 6 The difference from Example 1 is that the aluminum titanium silicon nitride layer is replaced by an aluminum titanium nitride layer.

[0081] A coated cemented carbide tool consists of a tool substrate and a coating. The coating is deposited on the surface of the tool substrate by a conventional chemical vapor deposition process.

[0082] 1. Tool base The tool matrix is ​​a tungsten carbide-based cemented carbide. The specific components of the tool matrix are: 90wt% tungsten carbide, 9wt% binder, 1wt% regulator, and the sum of the three mass percentages is 100wt%. Among them, the regulator is composed of vanadium carbide, ruthenium, and tantalum carbide in a mass ratio of 5:7:10; the binder is cobalt powder.

[0083] 2. Coating The coating is composed of a molybdenum sulfide layer, an aluminum nitride layer and an aluminum titanium nitride layer from the inside to the outside, wherein the relative atomic content of each element in the aluminum titanium nitride layer is Ti 35%, Al 20%, and N 45%.

[0084] The total thickness of the coating is 10 μm, of which the thickness of the molybdenum sulfide layer is 1 μm, the thickness of the aluminum nitride layer is 4 μm (4 times the thickness of the molybdenum sulfide layer), and the thickness of the aluminum titanium nitride layer is 5 μm (5 times the thickness of the molybdenum sulfide layer).

[0085] Comparative Example 7 The difference from Example 1 is that there is no ruthenium in the tool base. A coated cemented carbide tool consists of a tool substrate and a coating. The coating is deposited on the surface of the tool substrate by a conventional chemical vapor deposition process.

[0086] 1. Tool base The tool matrix is ​​a tungsten carbide-based cemented carbide. The specific components of the tool matrix are: 90wt% tungsten carbide, 9wt% binder, 1wt% regulator, and the sum of the three mass percentages is 100wt%. Among them, the regulator is composed of vanadium carbide and tantalum carbide in a mass ratio of 5:10; the binder is cobalt powder.

[0087] 2. Coating The coating is composed of a molybdenum sulfide layer, an aluminum nitride layer, and an aluminum titanium silicon nitride layer from the inside to the outside, wherein the relative atomic content of each element in the aluminum titanium silicon nitride layer is Ti 35%, Al 20%, Si 2%, and N 43%.

[0088] The total thickness of the coating is 10 μm, of which the thickness of the molybdenum sulfide layer is 1 μm, the thickness of the aluminum nitride layer is 4 μm (4 times the thickness of the molybdenum sulfide layer), and the thickness of the aluminum titanium silicon nitride layer is 5 μm (5 times the thickness of the molybdenum sulfide layer).

[0089] Comparative Example 8 The difference from Example 1 is that there is no tantalum carbide in the tool matrix. A coated cemented carbide tool consists of a tool substrate and a coating. The coating is deposited on the surface of the tool substrate by a conventional chemical vapor deposition process.

[0090] 1. Tool base The tool matrix is ​​a tungsten carbide-based cemented carbide. The specific components of the tool matrix are: 90wt% tungsten carbide, 9wt% binder, 1wt% regulator, and the sum of the three mass percentages is 100wt%. Among them, the regulator is composed of vanadium carbide and ruthenium in a mass ratio of 5:7; the binder is cobalt powder.

[0091] 2. Coating The coating is composed of a molybdenum sulfide layer, an aluminum nitride layer, and an aluminum titanium silicon nitride layer from the inside to the outside, wherein the relative atomic content of each element in the aluminum titanium silicon nitride layer is Ti 35%, Al 20%, Si 2%, and N 43%.

[0092] The total thickness of the coating is 10 μm, of which the thickness of the molybdenum sulfide layer is 1 μm, the thickness of the aluminum nitride layer is 4 μm (4 times the thickness of the molybdenum sulfide layer), and the thickness of the aluminum titanium silicon nitride layer is 5 μm (5 times the thickness of the molybdenum sulfide layer).

[0093] Performance Testing The coated blades of each embodiment and comparative example were tested after polishing. ① The Vickers hardness test refers to GB T7997-2014, and the test force is 294.2N (30kgf). ② The elastic modulus test was performed using a G200 nanoindenter (Anton Paar). ③ The conditions for the cutting test are: workpiece QT500, cutting speed 320m / min, feed 0.12mm / rev, cutting depth 1mm, cutting width 50mm, cutting method dry milling, and the average wear amount Vb of the blade back face exceeding 0.3mm or any blade wear Vbmax or chipping exceeding 0.3mm is selected as the life judgment standard. The results are shown in the following table.

[0094] As can be seen from the above table, the coated hard cutting tools prepared in each embodiment of the present invention have excellent comprehensive performance. Comparing Example 1 with Comparative Example 1, it can be seen that the coating can increase the hardness of the cutting tool by 27.4% and significantly extend the service life. Examples 1-3 are the best embodiments of the present invention. Compared with Example 1: The contents of each element in the aluminum titanium silicon nitride layer of Examples 4-6 are not within the preferred range, and the performance is reduced. Example 4 has a small amount of titanium, Example 5 has a small amount of aluminum, Example 6 has an excess of silicon, and Comparative Example 6 has no silicon. Titanium can improve hardness and interface bonding strength. Aluminum can improve corrosion resistance and wear resistance. Silicon is added to the aluminum titanium nitride layer to form a nanocrystalline (nc-TiAlN) / ​​amorphous (α-Si3N4) structure, which wraps around the main TiAlN nanocrystals as an interface phase, which can hinder the sliding of dislocations and the mutual sliding of grains, and block the diffusion of oxygen elements into the coating, thereby improving the hardness and high-temperature oxidation resistance of the coating. However, if the amount is excessive, the stress generated in the coating during the preparation process cannot be released, the fracture toughness is poor, and a thicker coating cannot be prepared.

[0095] Comparative Examples 2-4 lack one of the molybdenum sulfide, aluminum nitride, and aluminum titanium nitride silicon layers, respectively. Comparative Example 5 interchanges aluminum nitride and aluminum titanium nitride silicon. The tool life is significantly reduced, indicating that the three layers must cooperate with each other in a specific order to achieve better beneficial effects.

[0096] The thickness of each coating layer in Examples 7-10 is not within the preferred range, which affects the tool life. The thickness gradient increase setting in Examples 8-10 is lost, and the difference in thermal expansion coefficient generates thermal stress, and the interlayer bonding force and tool life are reduced.

[0097] In Comparative Examples 7 and 8, the lack of ruthenium or tantalum in the matrix not only affects the hardness and toughness of the matrix, but also reduces the bonding strength with the coating, and the tool life is seriously reduced. It can be seen that the matrix and the coating also need to cooperate with each other to play a good role.

[0098] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A coated cemented carbide tool, characterized in that: The tool substrate is a tungsten carbide-based cemented carbide containing VC, Ru, and TaC; the coating is a molybdenum sulfide layer, an aluminum nitride layer, and an aluminum titanium silicon nitride layer from the inside to the outside.

2. A coated cemented carbide tool according to claim 1, characterized in that: The relative atomic content of each element in the aluminum titanium silicon nitride layer is Ti 30-40%, Al 18-25%, Si 2-5%, and the balance is N.

3. A coated cemented carbide tool according to claim 2, characterized in that: The relative atomic content of each element in the aluminum titanium silicon nitride layer is Ti 35-40%, Al 20-25%, Si 2-3%, and the balance is N.

4. A coated cemented carbide tool according to claim 1, characterized in that: The total coating thickness is 5-10 μm.

5. A coated cemented carbide tool according to claim 4, characterized in that: The thickness of the molybdenum sulfide layer is 0.5-4 μm, the thickness of the aluminum nitride layer is 2-5 μm, and the thickness of the aluminum titanium silicon nitride layer is 2.5-7.5 μm.

6. A coated cemented carbide tool according to claim 1, 4 or 5, characterized in that: The thickness of the aluminum nitride layer is 2-4 times that of the molybdenum sulfide layer, and the thickness of the aluminum titanium silicon nitride layer is 5-8 times that of the molybdenum sulfide layer.

7. A coated cemented carbide tool according to claim 1, characterized in that: The coating is deposited by a chemical vapor deposition process.

8. The coated cemented carbide tool according to claim 1, characterized in that: The specific components of the tool matrix are: 82-91.5wt% tungsten carbide, 8-15wt% binder, 0.5-3wt% regulator, the sum of the mass percentages of the three is 100wt%, and the regulator is composed of VC, Ru, and TaC.

9. A coated cemented carbide tool according to claim 8, characterized in that: The mass ratio of VC, Ru and TaC in the regulator is (1-6):(5-8):

10.

10. A coated cemented carbide tool according to claim 8 or 9, characterized in that: The binder is selected from one or more of cobalt, iron, manganese, copper and nickel.

Citation Information

Cited By

  • Method for detecting service life of sharpening machine cutter and corresponding cutter structure

    CN121409785A

  • Wear-resistant anticorrosive coating on surface of sewage treatment impeller as well as preparation method and application of wear-resistant anticorrosive coating

    CN122503813A